Culturally based mathematics tasks: a framework for designing tasks from traditional Kven artefacts and knowledge - Huru, Hilja L.; Räisänen, Anna-Kaisa; Movik Simensen, Anita (NOMAD Nordic Studies in Mathematics Education, 2018)
This article discusses mathematical and cultural task design to support minority and endangered languages and cultures. More precisely, we propose a theoretical framework to design mathematical tasks for language immersion in mathematics for Kven students. Drawing on previous studies, we suggest that traditional tools have the potential to support the learning of mathematics, language, and culture. One challenge for endangered languages and cultures is that the younger generations may have lost connections with their traditional language and culture. We argue that the older generations can mediate authentic aspects of Kven culture to students, which then become historical-cultural authentic (HiCuA) aspects.